2016
DOI: 10.1007/978-3-319-33461-5_17
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Cut-Generating Functions are Nearly Extreme

Abstract: We study continuous (strongly) minimal cut generating functions for the model where all variables are integer. We consider both the original Gomory-Johnson setting as well as a recent extension by Cornuéjols and Yıldız. We show that for any continuous minimal or strongly minimal cut generating function, there exists an extreme cut generating function that approximates the (strongly) minimal function as closely as desired. In other words, the extreme functions are "dense" in the set of continuous (strongly) min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 17 publications
(37 reference statements)
0
20
0
Order By: Relevance
“…Note that a polyhedron P has a finite number of facet-defining inequalities and, excluding degenerate cases, infinitely many minimal inequalities; thus, restricting to facet-defining inequalities really narrows down the inequalities under consideration. However, interestingly, for the infinite group relaxation (which is infinite dimensional), it was recently proved that the facet-defining inequalities form a dense set within the set of minimal inequalities [48,163]. This casts doubts on whether being a facet-defining inequality is really useful in this context.…”
Section: Theoretical Analysis Of the Strength Of Cutting-planesmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that a polyhedron P has a finite number of facet-defining inequalities and, excluding degenerate cases, infinitely many minimal inequalities; thus, restricting to facet-defining inequalities really narrows down the inequalities under consideration. However, interestingly, for the infinite group relaxation (which is infinite dimensional), it was recently proved that the facet-defining inequalities form a dense set within the set of minimal inequalities [48,163]. This casts doubts on whether being a facet-defining inequality is really useful in this context.…”
Section: Theoretical Analysis Of the Strength Of Cutting-planesmentioning
confidence: 99%
“…As mentioned above, other recent papers [48,163] considered the question of separating faces versus facet-defining inequalities in the context of the (infinite) group relaxation. Surprisingly, it was shown that for any minimal inequality, there exists an extreme inequality that approximates the minimal inequality as closely as desired.…”
Section: Cutting-plane Selection: the Need To Ask Different Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of Gomory-Johnson cut-generating functions, the 2-slope theorem is a famous result of Gomory and Johnson's masterpiece [10,11]. Basu et al [8] proved that the 2-slope extreme Gomory-Johnson cut-generating functions are dense in the set of continuous minimal functions. We show that any 2-slope maximal general DFF with one slope value 0 is extreme.…”
Section: Introductionmentioning
confidence: 99%
“…This result is a key step in our approximation theorem, which indicates that almost all continuous maximal general DFFs can be approximated by extreme (2-slope) general DFFs as close as we desire. Unlike the 2-slope fill-in procedure Basu et al [8] used, we always use 0 as one slope value in our fill-in procedure, which is necessary since the 2-slope theorem of general DFFs requires 0 to be one slope value. This paper is structured as follows.…”
Section: Introductionmentioning
confidence: 99%